Dancing intercorporeality: a health humanities perspective on dance as a healing art - Purser, Aimie Christianne Elizabeth. (Springer, 2017)
As a contribution to the burgeoning field of health humanities, this paper seeks to explore the power of dance to mitigate human suffering and reacquaint us with what it means to be human through bringing the embodied practice of dance into dialogue with the work of the French philosopher Maurice Merleau-Ponty. Merleau-Ponty’s conceptualisation of subjectivity as embodied and of intersubjectivity as intercorporeality frees us from many of the constraints of Cartesian thinking and opens up a new way of thinking about how dance functions as a healing art through its ability to ground and reconnect us with self, world, and others; with our humanity. It is argued that through this Merleau-Pontian framework we can therefore come to appreciate the true potential of dance as a positive and deeply humanising experience, thus demonstrating how expressive arts practice understood through the lens of philosophical theory can open up new dimensions of understanding and experience in relation to well-being and self- (and other-) care.